The role of situational context and linguistic context when testing EFL vocabulary knowledgde in a language teacher education program: a preliminary approach - Franco, Claudia Patricia; Galvis, Hector Alejandro (Colombian Applied Linguistics Journal, 2013)
This research aims to provide a preliminary approach on to what extent linguistic and situational contexts are conducive to successful vocabulary recognition in discrete-item testing in the context of a language teacher education program in Bogotá. This study resorted to the use of four different types of vocabulary tests administered during a one-semester period to two different classes. The data collected revealed that students had more success in a test of productive vocabulary (L2 to L1 translation) than in other types of tests, namely, productive vocabulary (L2 to L1 translation/multiple choice), L2 to L1 translation provided with linguistic context and cued situational context. The findings of this research suggest that the participating pre-service teachers had not reached the basic vocabulary knowledge of the English Language at the time of this study. It was also found that vocabulary items devoid of contextual cues are more accurately identified than those embedded within a linguistic context and a cued situational context.